1936
DOI: 10.1111/j.1469-1809.1936.tb02136.x
|View full text |Cite
|
Sign up to set email alerts
|

ON THE LINKAGE RELATIONS OF THE GENES FOR ALLERGIC DISEASE AND THE GENES DETERMINING THE BLOOD GROUPS, MN TYPES AND EYE COLOUR IN MAN

Abstract: The articles published by the Annals of Eugenics (1925–1954) have been made available online as an historical archive intended for scholarly use. The work of eugenicists was often pervaded by prejudice against racial, ethnic and disabled groups. The online publication of this material for scholarly research purposes is not an endorsement of those views nor a promotion of eugenics in any way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1937
1937
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…An analysis of our own (5,6) family studies (66 complete families with 250 children), as well as data already published, failed to support either the simple dominant or recessive theory. The dominant theory does not explain why in more than half of the pedigrees both parents are normal.…”
mentioning
confidence: 68%
“…An analysis of our own (5,6) family studies (66 complete families with 250 children), as well as data already published, failed to support either the simple dominant or recessive theory. The dominant theory does not explain why in more than half of the pedigrees both parents are normal.…”
mentioning
confidence: 68%
“…Another sib‐pair linkage investigation reported that “one hundred and seventy one possible linkage relations were tested from data involving nineteen traits and 903 sib‐pairs” (Kloepfer, 1946), and an attempt to replicate previous linkage findings concluded that “no signs of linkage were found between ‘strikingly red hair’ and the blood groups ABO, MN, P, Lewis, Duffy, Kell and Rhesus, taste sensitivity to PTC., eye colour, and sex” (Hauge & Helweg‐Larsen, 1954). Another publication on allergy versus blood groups and eye color also “failed to reveal any evidence of linkage among the genes determining these traits” (Zieve et al, 1936). In those exciting times of applying the new tool of linkage analysis, it was evidently commonplace to report positive as well as negative linkage findings.…”
Section: A Quarter Century Of Linkage Papersmentioning
confidence: 99%
“…Statistical analysis failed to reveal any evidence of linkage among the genes determining these traits (6).…”
Section: The Inheritance Of Allergic Disease* Alexander S Wiener Prementioning
confidence: 99%